(The ultimate sticker book) Cat (Dorling Kindersley Publishing, New York, NY, 1993)
The Ultimate Cat Sticker Book is a fun and interactive collection designed for cat lovers of all ages. It features a wide range of stickers depicting various breeds of cats, their behaviors, and fun facts. The book offers over 60 reusable stickers that can be used to create personalized cat scenes or for educational purposes. Alongside the stickers, there are descriptions of different cat types, their origins, habits, and care tips, making it an engaging and informative tool for learning about cats while enjoying a creative activity.